PENGARUH PERUBAHAN ORGANISASI PADA KINERJA PEGAWAI DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MEDIASI (The Effect of Organizational Change on Employee Performance with Organizational Culture as a Mediating Variable) - Verry Fahrudin; Nurwati Nurwati; Salma Saleh (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The purpose of this study is to examine and explain the effect of organizational change on employee performance with organizational culture as a mediating variable at the UPTP Ministry of Manpower in Kendari. The approach of this research is a survey with explanatory research design. Data collection was carried out using survey methods through questionnaires and interviews. The study population was 62 employees at the UPTP Ministry of Manpower in Kendari. Because the population in this study is relatively small, all populations in the study are made as respondents. The analytical equipment used is Partial Least Square (PLS).The results showed that the effect of organizational change had a positive and significant effect on organizational culture; organizational culture has a positive and significant effect on employee performance; organizational change has a negative and not significant effect on employee performance, and organizational culture can mediate well between organizational change variables and employee performance.